A Four-Part Model of Informal Learning: Extending Schugurensky's Conceptual Model - Elizabeth E. Bennett (Adult Education Research Conference, 2012)
Adults are learning all the time, especially in an era of knowledge work in which lifelong learning is integral to the economy (Bennett & Bell, 2010). Technology is offering unprecedented access to new information and to knowledge communities, and there is a great need for adults to learn informally to keep up with the fast pace of life. This paper examines informal learning and proposes an extension of Schugurensky‘s (2000) typology, which Merriam, Caffarella, & Baumgartner (2009) describe as occurring in natural settings with learner direction, even if the learner does not recognize learning is occurring. The extension adds another form of informal learning, integrative learning, to conceptualize a four-part model of informal learning that is supported by implicit processing literature in Psychology.